Ultrasound-guided erector spinae plane block versus oblique subcostal transversus abdominis plane block for postoperative analgesia of adult patients undergoing laparoscopic cholecystectomy: Randomized, controlled trial - Altıparmak, Başak; Korkmaz Toker, Melike; Uysal, Ali Ihsan; Kuşçu, Yağmur; Gümüş Demirbilek, Semra (Journal of clinical anesthesia, 2019)
Laparoscopic cholecystectomy (LC) is a frequently applied minimally invasive surgery. Intraoperative access is provided with small keyhole entries on the abdominal wall. However, LC causes moderate to severe postoperative pain. The subcostal approach of TAP block was described by Hebbard et al. for postoperative analgesia especially for upper abdominal surgeries. Ultrasound-guided erector spinae plane (US-ESP) block is a novel technique targeting ventral rami, dorsal rami and rami communicantes of the spinal nerves. Single-blinded, prospective, randomized study. Tertiary university hospital, postoperative recovery room and surgical ward. Seventy-six patients (ASA I-II) were divided into two equal groups. After applying the exclusion criteria, 68 patients were included in final analysis (34 patients in ESP group and 34 in OSTAP group). Erector spinae plane block was performed in the ESP group and oblique subcostal transversus abdominis block was performed in the OSTAP group. Measurements: Postoperative tramadol consumption and pain scores between groups were compared. In addition, intraoperative fentanyl need was measured. Postoperative tramadol consumption was 139.1 ± 21.9 mg in the ESP group and 199.4 ± 27.7 mg in the OSTAP group (mean difference 60.29 mg, 95% confidence interval - 72.40 to - 48.19; p < 0.001). NRS scores at almost all time-points were lower in the ESP group according to the repeated measures analysis. Integration of AUC and Mann Whitney U test results have revealed that there was no time wise difference between ESP and OSTAP groups even though NRS scores by itself and time-wise linear area under curve scores were higher in the OSTAP group compare to ESP group. There were no differences in intraoperative fentanyl need. Ultrasound-guided ESP block reduced postoperative tramadol consumption and pain scores more effectively than OSTAP block after laparoscopic cholecystectomy surgery. •Laparoscopic cholecystectomy causes moderate to severe postoperative pain.•OSTAP block provides analgesia especially for upper abdominal surgeries.•ESP is a novel block which extends cranially and caudally over several dermatomal levels.•Both ESP and OSTAP blocks are effective for analgesia after cholecystectomy.